Let's look at winter - Schuette, Sarah L., 1976- (Mankato, Minn. : Capstone Press, 2007)
Investigates the signs that say it is winter, looking at the changes in the weather, length of days, and the behavior of plants and animals.
Includes bibliographical references (p. 23) and index.
Library Media Connection
School Library Journal
Wilson's Children
Library Media Connection, October 2007
School Library Journal, May 2007
Keywords: Animal behavior -- Juvenile literature; Winter -- Juvenile literature; Animal behavior; Winter; Animal behavior; Winter; Readers (Elementary).